Counseling Adolescents About Contraception: Towards the Development of an Evidence-Based Protocol for Contraceptive Counselors - Jaccard, James; Levitz, Nicole (Journal of adolescent health, 2013)
Research on contraceptive counseling of adolescents in clinics and service delivery settings is considered. The provider context as well as the developmental context of adolescence is characterized and their implications for contraceptive counseling are explicated. After reviewing research on the effectiveness of contraceptive counseling, it was concluded there is little empirical evidence to support the efficacy of current practices considered as a totality. Twelve principles for effective contraceptive counseling were then derived as a basis for building an evidence-based contraceptive counseling protocol for adolescents.